Peningkatan Kapabilitas UMKM Kuliner di Kota Malang Melalui Pelatihan Manajemen Kualitas - Wiwik Handayani; Irma Kurniasari; Muhammad Bhirawa Dwi Atma Citalada; Septian Sony Utomo; Vian Ahmad Saputra (Asthadarma : Jurnal Pengabdian Kepada Masyarakat, 2024)
The Community Service Activity carried out by the Universitas Pembangunan Nasional Veteran Jawa Timur aims to increase the capacity of culinary Micro, Small, and Medium Enterprises (MSMEs) in Malang City through quality management training. The research stages include preparation, implementation, and evaluation. In the preparation stage, a mapping of the current conditions of culinary MSMEs is carried out to identify their specific needs. The implementation stage focuses on training that includes product quality management and effective financial management. Evaluation is carried out through further assistance to assess the extent of understanding and application of training materials by MSME actors. Community service activities show that this training significantly increases MSME understanding in maintaining product quality and managing finances, so as to increase the competitiveness and sustainability of their businesses.